Speckle referencing: digital speckle pattern interferometry (SR- DSPI) for imaging of non-diffusive surfaces - Matham, Murukeshan Vadakke (2018)
Optical metrology has been widely employed as a key technique for modern industrial production, owing to its fast, precise and non-invasive measurement. Digital speckle pattern interferometry (DSPI) is one of these non-destructive testing methods that possess the abilities to measure surface deformation, vibration and profile. However, one of the challenges with DSPI is the incapability to address the imaging of non-diffusive surface, owing to the failure to form speckle pattern. In this paper, we demonstrate a modified DSPI system used for non-diffusive surface measurement. Experiment has been carried out to validate this modified DSPI by using metal-alloy surface as testing sample. The speckle fringe pattern generated by applying an external load was analyzed to obtain the 3-D surface deformation parameters.